2005
DOI: 10.1158/1078-0432.ccr-04-2405
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Expression Correlates with Local Chronic Inflammation and Tumor Neovascularization in Human Prostate Cancer

Abstract: Purpose: Chronic inflammation is linked to the development of cancer in several organs, including the prostate. Up-regulated cyclooxygenase-2 (COX-2) may play a role in influencing cell proliferation, differentiation, apoptosis, or angiogenesis.This study aimed to derive data from human prostate cancer to investigate whether chronic inflammation and angiogenesis were correlated with the expression of COX-2. Experimental Design: In this study, we did double-immunohistochemical analysis of a set of 43 human pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
92
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 44 publications
8
92
0
4
Order By: Relevance
“…The second isoform of COX (COX-2) is frequently up-regulated in various cancers, including prostate cancer (1). Oncogenes such as ras or Her-2 stimulate COX-2 expression (2), whereas tumor suppressors such as p53 down-regulate COX-2 expression (3).…”
Section: Introductionmentioning
confidence: 99%
“…The second isoform of COX (COX-2) is frequently up-regulated in various cancers, including prostate cancer (1). Oncogenes such as ras or Her-2 stimulate COX-2 expression (2), whereas tumor suppressors such as p53 down-regulate COX-2 expression (3).…”
Section: Introductionmentioning
confidence: 99%
“…Through the production of prostaglandins, COX2 is hypothesised to influence carcinogenesis by promoting cell proliferation, inhibiting apoptosis, stimulating angiogenesis, and mediating immune suppression (Kirschenbaum et al, 2001;Fujita et al, 2002;Nithipatikom et al, 2002;Wang et al, 2005). Multiple studies have shown increased expression of COX2 in prostate tumours (Gupta et al, 2000;Kirschenbaum et al, 2000;Tanji et al, 2000;Yoshimura et al, 2000;Uotila et al, 2001), although one study reported overexpression not in tumour tissue but rather in proliferative inflammatory atrophy, a putative precursor lesion of prostate cancer (Zha et al, 2001).…”
mentioning
confidence: 99%
“…Multiple studies have shown increased expression of COX2 in prostate tumours (Gupta et al, 2000;Kirschenbaum et al, 2000;Tanji et al, 2000;Yoshimura et al, 2000;Uotila et al, 2001), although one study reported overexpression not in tumour tissue but rather in proliferative inflammatory atrophy, a putative precursor lesion of prostate cancer (Zha et al, 2001). More recently, increased COX2 expression has been correlated with higher tumour grade (Wang et al, 2005) and prostate cancer progression (Cohen et al, 2006). Nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit the enzymatic activity of COX2, and inhibitors of COX2 suppress the growth of prostate cancer cells in vitro as well as prostate tumorigenesis in vivo Gupta et al, 2004;Patel et al, 2005;Narayanan et al, 2006).…”
mentioning
confidence: 99%
“…Cyclooxygenase 2 is an enzyme that converts arachidonic acid to prostaglandins, which are potent mediators of inflammation. [34][35][36][37] Similarly, IkB kinase-a-activation reduces the infiltration of RANK ligand-expressing inflammatory cells and is associated with metastasis of prostate cancer in mice. 38 These observations suggest a combined role of gene, environment (macro and micro) and immunity in the development of prostate cancer.…”
Section: Hoop Of Gene Environment and Immune Systemmentioning
confidence: 99%